PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DENGAN MEDIA VIDEO UNTUK MENINGKATKAN KERJASAMA DAN HASIL BELAJAR SEJARAH SISWA SMA - Nafisah, Eka Assyatun; Musadad, Akhmad Arif; Isawati, Isawati (Program Studi Pendidikan Sejarah FKIP Unversitas Sebelas Maret, 2018)
The main objectives of this study are to improve students? cooperation and learning outcomes of class XI IPA 1 SMA Muhammadiyah 1 Karanganyar through the implementation of cooperative learning model Numbered Heads Together by using video as media in history subject. Classroom action research was applied in this study through two cycles. Each cycle consisted of four stages namely planning, action, observation and reflection. The sample of this study was 39 students of class XI IPA 1 SMA Muhammadiyah 1 Karanganyar. Sources of data used in this study were informants, places or locations, events and documents. Technique of collecting data was done by observation, questionnaire, test, interview and documentation. Triangulation was used to validate the data. The data were analyzed by using qualitative and quantitative descriptive analysis. This study uses spiral model (planning, action, observation and reflection) by Kemmis and Mc. Taggar model.The results of research show that students? cooperation increased in each cycle, in the pre-cycle stage there were 22 students having high cooperation with 56.41%. In the first cycle, students having high-cooperation category increased up to 27 students with percentage of 69.23%. In cycle two, students having high cooperation increased up to 33 students with percentage of 84.62%. Student learning outcomes also increased. In pre-cycle stage, the number of students who passed the passing grade were 10 students with the percentage of 25.64%. Then in first cycle, the number of students who get the above the passing grade were 21 students with 53.85% percentage. In cycle two, the number of students who passed the passing grade were 34 students or 87.18%. The acquisition is the goal that determined to exceed that 80%.